2012
DOI: 10.1103/physrevlett.109.190404
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Metrological Limits via a Variational Approach

Abstract: The minimum achievable statistical uncertainty in the estimation of physical parameters is determined by the quantum Fisher information. Its computation for noisy systems is still a challenging problem. Using a variational approach, we present an equation for obtaining the quantum Fisher information, which has an explicit dependence on the mathematical description of the noise. This method is applied to obtain a useful analytical bound to the quantum precision in the estimation of phase-shifts under phase diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
155
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(166 citation statements)
references
References 31 publications
9
155
2
Order By: Relevance
“…In the following, we address this question using the variational approach to the method of purifications introduced in Ref. [18].…”
Section: Non-dissipative Phase-diffusion Noisementioning
confidence: 99%
See 4 more Smart Citations
“…In the following, we address this question using the variational approach to the method of purifications introduced in Ref. [18].…”
Section: Non-dissipative Phase-diffusion Noisementioning
confidence: 99%
“…In Ref. [18] it was shown that the ultimate precision bound for a linear estimation scheme affected by phase diffusion contains a constant term independent of the average number of photons N . Hence, it is believed that the presence of phase diffusion is even more detrimental to the performance of linear estimation than the presence of photon loss.…”
Section: Non-dissipative Phase-diffusion Noisementioning
confidence: 99%
See 3 more Smart Citations